Preface: BITS2014, the annual meeting of the Italian Society of Bioinformatics. Issue 9 (December 2015) - Facchiano, Angelo; Angelini, Claudia; Bosotti, Roberta; Guffanti, Alessandro; Marabotti, Anna; Marangoni, Roberto; Pascarella, Stefano; Romano, Paolo; Zanzoni, Andreas; Helmer-Citterich, Manuela
Abstract This Preface introduces the content of the BioMed Central journal Supplements related to BITS2014 meeting, held in Rome, Italy, from the 26th to the 28th of February, 2014.